Follicular lymphoma grade 3B is a distinct neoplasm according to cytogenetic and immunohistochemical profiles - Horn, Heike (Ferrata Storti Foundation, 2011)
BACKGROUND: According to the current World Health Organization Classification of Lymphoid Tumours, follicular lymphoma is subclassified into three grades according to the number of centroblasts. Follicular lymphoma grade 3 can be further divided into types A and B. Almost all available genetic data on grade 3B follicular lymphomas have been generated from tumors with an additional diffuse large B-cell lymphoma component. The purely follicular type of follicular lymphoma grade 3B is a rare neoplasm. DESIGN AND METHODS: We performed a detailed immunohistochemical (CD10, IRF4/MUM1, BCL2, Ig light chains) and genetic (translocations of BCL2, BCL6, MYC, IRF4) characterization of the largest series of purely follicular cases of grade 3B follicular lymphoma available to date, comprising 23 tumor samples. We also included 25 typical grade 1 or 2 follicular lymphomas, 9 follicular lymphomas with large centrocytes and/or high proliferation indices (FL/LCC), 12 cases of follicular lymphoma grade 3A, 16 cases of diffuse large B-cell lymphoma/follicular lymphoma grade 3B and 15 follicular lymphomas in which a straightforward distinction between grades 3A and 3B was not possible. RESULTS: Translocations affecting BCL2 and BCL6 genes are rare in grade 3B follicular lymphomas (2/23, 9% and 4/23, 17%) when compared with grade 1 or 2 follicular lymphomas (22/25, 88%, P<0.001 and 0/25, P<0.05), FL/LCC (7/9, 78%, P<0.001 and 2/9, 22%), grade 3A follicular lymphomas (7/12, 58%, P<0.01 and 2/12, 17%), unclassified grade 3 follicular lymphomas (6/15, 40% and 2/15, 13%) and diffuse large B-cell lymphoma/follicular lymphoma grade 3B (2/16, 13% and 8/16, 50%, P<0.05). MYC translocations were detected occasionally in FL/LCC, follicular lymphoma grade 3B, and diffuse large B-cell lymphoma/follicular lymphoma grade 3B (13%–22%), but not in grade 1, 2 or 3A follicular lymphomas (P<0.05 when compared with follicular lymphoma grade 3B). Both follicular lymphoma grade 3B and diffuse large B-cell lymphoma/follicular lymphoma grade 3B were enriched in samples with a CD10(−)IRF4/MUM1(+) immunophenotype (8/19, 42% and 7/16, 44%), with the vast majority of them lacking BCL2 translocations. In contrast, 42/46 grade 1 or 2 follicular lymphomas, FL/LCC and grade 3A follicular lymphomas were CD10(+) (91%) while 0/46 expressed IRF4/MUM1. None of the tumor samples tested with increased IRF4/MUM1-expression harbored a translocation of the IRF4 gene locus. CONCLUSIONS: Our results show that grade 3B follicular lymphomas form a distinct category of follicular lymphomas with infrequent BCL2 and BCL6 translocations, while grades 1, 2 and 3A follicular lymphomas and FL/LCC display homogeneous features with frequent BCL2 translocations and a CD10(+)IRF4/MUM1(−) immunophenotype.